Generosity in Leadership' women's lunch Dec. 13 - Uribes, Tom::::::::: (2013)
Dr. Christine Edmondson, Fresno State Psychology professor, will discuss 'Effective Use of Generosity in Leadership' at the Women's Campus Connection luncheon